Two nitrate/nitrite transporters are encoded within the mobilizable plasmid for nitrate respiration of Thermus thermophilus HB8 (2000)
Thermus thermophilus HB8 can grow anaerobically by using a membrane-bound nitrate reductase to catalyze the reduction of nitrate as a final electron acceptor in respiration. In contrast to other denitrifiers, the nitrite produced does not continue the reduction pathway but accumulates in the growth medium after its active extrusion from the cell. We describe the presence of two genes,narK1 and narK2, downstream of the nitrate reductase-encoding gene cluster (nar) that code for two homologues to the major facilitator superfamily of transporters. The sequences of NarK1 and NarK2 are 30% identical to each other, but whereas NarK1 clusters in an average-distance tree with putative nitrate transporters, NarK2 does so with putative nitrite exporters. To analyze whether this differential clustering was actually related to functional differences, we isolated derivatives with mutations of one or both genes. Analysis revealed that single mutations had minor effects on growth by nitrate respiration, whereas a double narK1 narK2 mutation abolished this capability. Further analysis allowed us to confirm that the double mutant is completely unable to excrete nitrite, while single mutants have a limitation in the excretion rates compared with the wild type. These data allow us to propose that both proteins are implicated in the transport of nitrate and nitrite, probably acting as nitrate/nitrite antiporters. The possible differential roles of these proteins in vivo are discussed.